2015
DOI: 10.12739/nwsa.2015.10.3.4c0197
|View full text |Cite
|
Sign up to set email alerts
|

Social Medi̇a as a Means Used in Interpersonal Communi̇cati̇on: A Research Ori̇ented Onto the Students of Gümüşhane Uni̇versity Faculty of Communi̇cati̇On

Abstract: Günümüzde internetin yaygınlaşması ile birlikte, sosyal ağlar ve sosyal medya ortamları insanoğlunun vazgeçilmez paylaşım alanları olmuştur. Gelinen bu süreçte kişilerarası iletişim de yüz yüze yapılmaktan çok, sosyal medya üzerinden gerçekleşmeye başlamıştır. Dolayısıyla iletişim zamanla yüz yüze olmaktan çıkarak, sosyal medya aracılığıyla gerçekleşir hale dönüşmüştür. Çalışmada sosyal medyanın yaygınlaşmasıyla birlikte, kişilerarası iletişime katkısının ne yönde olduğunu, kişilerarası iletişim aracı olarak s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…It is known that among users, especially the younger age group faces the risk of addiction. Although social media is regarded as a new area of socialization and that this situation is an advantage (Savcı & Aysan, 2017 ), it is also reported that social media has a negative effect on interpersonal relationships (Çalışır, 2015 ), psychological health (Chen et al, 2020 ) and private life (Acılar & Mersin, 2015 ), increases levels of depression (Haand & Shuwang, 2020 ), and leads to social media addiction. Indeed, it has been determined that in the case of adolescent users, excessive levels of use are associated with paranoid thoughts, phobic anxiety and feelings of anger and hostility (Bilgin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that among users, especially the younger age group faces the risk of addiction. Although social media is regarded as a new area of socialization and that this situation is an advantage (Savcı & Aysan, 2017 ), it is also reported that social media has a negative effect on interpersonal relationships (Çalışır, 2015 ), psychological health (Chen et al, 2020 ) and private life (Acılar & Mersin, 2015 ), increases levels of depression (Haand & Shuwang, 2020 ), and leads to social media addiction. Indeed, it has been determined that in the case of adolescent users, excessive levels of use are associated with paranoid thoughts, phobic anxiety and feelings of anger and hostility (Bilgin, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was similarly seen in the study that the pessimism subscale scores of the adolescents who spent 0-2 hours/day on social media were higher than those who used social media for 9 hours/day. It is reported that social media has a negative affect on interpersonal relationships 26 and psychological wellbeing. 27 Adolescents whose daily usage durations are high also exhibit high depression levels 24 , and it is reported that there is a positive correlation between anxiety and depression levels and daily social media usage durations.…”
Section: Discussionmentioning
confidence: 99%
“…Students who spend a lot of time on the internet and social media applications can be influenced by these applications and break away from social life (16). In addition, it has been stated that social media negatively affects interpersonal relationships (17), psychological health (18), and private life (19). In light of all these considerations, the aim of this study is to investigate the relationship between social media addiction and physical activity levels in adolescents.…”
Section: Introductionmentioning
confidence: 99%